2018
DOI: 10.1111/josl.12304
|View full text |Cite
|
Sign up to set email alerts
|

The pragmatics of kin address: A sociolinguistic universal and its semantic affordances

Abstract: This paper focuses on an understudied sociolinguistic variable – the use of proper names as opposed to kin terms in address. We present findings from a survey of 80 speech communities that reveals a striking regularity in the way these two noun‐phrase types are used. Where kin terms alternate with names in address, kin terms are always used for senior kin and names for junior kin. The strong cross‐cultural uniformity of this alternation is not easily accounted for by reference to culture‐specific language ideo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Lastly, we found that more borrowings take place in affinal kin categories and in categories denoting relatives older than ego, suggesting that these are the dimensions where the changes in kinship terminologies initiate. Changes in kin terms denoting more senior relatives may be connected with the cross-cultural finding that younger relatives address them more often with a kin term, whereas the seniors are more likely to use personal names to address their younger relatives (Fleming and Slotta, 2018). Young people are typically seen as the innovators in situations of language change (Labov, 2001), thus they could be suggested to have a role also in the borrowings of kinship terms.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we found that more borrowings take place in affinal kin categories and in categories denoting relatives older than ego, suggesting that these are the dimensions where the changes in kinship terminologies initiate. Changes in kin terms denoting more senior relatives may be connected with the cross-cultural finding that younger relatives address them more often with a kin term, whereas the seniors are more likely to use personal names to address their younger relatives (Fleming and Slotta, 2018). Young people are typically seen as the innovators in situations of language change (Labov, 2001), thus they could be suggested to have a role also in the borrowings of kinship terms.…”
Section: Discussionmentioning
confidence: 99%
“…14. Fleming and Slotta (2018), in their investigation into terms of address, find the crosscultural predominance of this pattern of address, whereby kin terms are employed for generations above ego (due to the honorific character of these lexical expressions), and proper names for the younger generation ("anti-honorifics"). 15.…”
Section: Consanguineal Kin Terminologymentioning
confidence: 99%
“…Importantly, kinship relationality is signified in a quite distinct way here than in the kinship restricted systems that we looked at above. In these cases, the T‐V distinction diagrams a hierarchical, asymmetric schema of seniority within the cognatic kin group (Fleming and Slotta 2018), rather than a symmetric schema of mutual avoidance like the one found in T‐V systems restricted to in‐laws, to cross‐sex siblings, or to members of disharmonic generations. (Observe, however, that in hierarchical systems, V is often employed reciprocally between affinal relations, for instance in Tamil [Levinson 1982] and Yemsa.…”
Section: Fractal Hierarchical T‐v Systemsmentioning
confidence: 99%